Pleural Disease in Women - Argento, Angela Christine; Gillespie, Colin T. (Seminars in Respiratory and Critical Care Medicine, 2019)
There are several pleural diseases that occur either predominantly or exclusively in females. Most of these entities are related to obstetric or gynecological conditions. In this article, we will provide an overview of Meigs' syndrome, ovarian hyperstimulation syndrome, endometriosis, catamenial pneumothorax, catamenial hemothorax, pleural effusions that occur in the peripartum period, lymphangioleiomyomatosis, and malignant pleural effusions related to breast cancer. As most of these diagnoses are rare, considerable expertise is required to identify, diagnose, and manage these patients. The aim of this article is to present an overview of the most common forms of pleural disease affecting women, and to provide an easy reference source on current best practice.
Keywords: pleural disease; women; pleural effusion; pneumothorax; hemothorax; catamenial; Meigs' syndrome; breast cancer; ovarian hyperstimulation syndrome